Complete chloroplast genome sequence of Chrysosplenium sinicum and Chrysosplenium lanuginosum (Saxifragaceae) - Rui Liao; Xiang Dong; Zhi-Hua Wu; Rui Qin; Hong Liu (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome of Chrysosplenium sinicum Maxim and Chrysosplenium lanuginosum Hook. f. et Thoms. were reported in this study. The chloroplast genomes were 152,524 bp and 151,512 bp for C. sinicum and C. lanuginosum, respectively. LSC and SSC of 83,330 bp and 18,018 bp were separated by two IRs of 25,588 bp each in C. sinicum. While C. lanuginosum contained IRs of 25,985 bp, LSC of 82,250 bp and SSC of 17,292 bp, for a total 151,512 bp length. The chloroplast genomes both contained 117 genes, including 82 protein-coding genes, 31 tRNA genes, and four rRNA genes.